Retinal detachment in identical twins with Stickler syndrome type 1. Issue 11 (November 1996) - Watanabe, Y; Ueda, M; Adachi-Usami, E
Abstract : BACKGROUND: The high incidence of retinal detachment and its poor surgical prognosis in patients with Stickler syndrome are well known. However, the vitreoretinal relation to retinal detachment in this syndrome is uncertain. METHODS: Vitreoretinal examination with a binocular indirect ophthalmoscope and a Goldmann three mirror contact lens was performed on identical twin boys with Stickler syndrome. Each had retinal detachment in the left eye, and many aspects of their fundus findings were similar. The vitreous showed distinct abnormalities consistent with congenital vitreous anomaly of type 1 Stickler syndrome. The twins were followed up for 4 years after undergoing a successful operation to reattach their left retinas. RESULTS: Rhegmatogenous detachment with multiple tears occurred in the right eye of only one twin during the follow up period, despite the similar condition of their fundi. Although vitreous body was not present in most parts, slightly opaque vitreous cortex was attached to the retina near the ora serrata, and neither twin had posterior vitreous detachment during the follow up period. CONCLUSION: Multiple retinal tears appeared simultaneously in the right eye of one twin, indicating some tractional force had acted on the retina. It is believed that this force was caused by very thin vestigial vitreous cortex attached to the retina. Although these observations have been limited, vitreoretinal findings of the twins and their father were consistent and suggested presence of thin vitreous cortex attached to the retina without posterior vitreous detachment.